The Relationship between Inflation and its Uncertainty: Evidence from Jordan - Ananzeh, Izz Eddien N. (International Journal of Economics and Financial Issues, 2015)
There are many harmful impacts of inflation and inflation volatility in any economy, which includes increasing the risk premium, costs of hedging, and consequently leads to re-distribution of national income between strata of society unfairly. Therefore, this study came to test the relationship between inflation and inflation uncertainty for Jordan from 1976 to 2013. For that purpose we employing two different methodologies generalized autoregressive conditional heteroscedasticity GARCH process, and the granger causality technique. The results of the GARCH model support the hypothesis of Friedman & Ball through Indicating strong support for the presence of a positive relationship between the inflation rate and its uncertainty. The Granger causality results report supporting hypothesis of Cukierman and Meltzer in 1986, and also Granger causality test running in the both ways. Keywords: GARCH model; Granger Causality Test; Inflation; Inflation Uncertainty JEL Classifications: C1; D8; E31